PENGGUNAAN WEBSITE WKWK JAPAN DALAM PEMBELAJARAN MANDIRI PADA MATA KULIAH NIHONGO SHOKYUU PADA MASA PANDEMI COVID-19 - Sukma Urwafull Usqo Septiani; Hadriana Hadriana; Merri Silvia Basri (Undiksha Press, 2022)
Independent learning is a person's readiness or willingness to learn independently which consists of an attitude component that takes the initiative to learn with or without the help of others. This study aims to find out how the use of the WKWK Japan website in independent learning based on the generative theory by Huda (2014) in the Nihongo Shokyuu course by Japanese Language Education students FKIP UNRI batch 2020. This study uses a qualitative descriptive method. The research was conducted by conducting interviews with data sources. The data sources in this study were 7 students of the 2020 Japanese Language Education FKIP Riau University who took the Nihongo Shokyuu class and used the WKWK Japan website in independent learning. The results of this study indicate that the class of 2020 students use independent learning strategies according to Huda (2014) in various ways in each strategy.